Is tramadol associated to bleeding peptic ulcer? A nationwide case-control study in hospitalized Swedish patients - Järnbert-Pettersson, Hans (PLoS One, 2019)
AIMS: Tramadol, a widely used analgesic drug, inhibits the reuptake of noradrenaline and serotonin impairing the aggregation function of thrombocytes. However, the risk for severe bleeding has previously not been studied. The aim of the present study is to investigate the association between tramadol and bleeding peptic ulcer in the Swedish population. METHODS: In this register based case–control study based on the Swedish national patient registry and prescription drug registry, we included 18 306 patients hospitalized with a first-time diagnosis of bleeding peptic ulcer. For every case, 4 matched controls were included. To investigate the temporal aspects of tramadol induced bleeding ulcer, exposure was divided into patients with newly initiated and ongoing treatment. To explore a possible confounding by indication, the effect of codeine, a drug also prescribed for the treatment of moderate pain, but not known to affect thrombocyte function, was investigated. Univariable and multivariable logistic regression was used to analyse the association between tramadol use and bleeding ulcer. RESULTS: Tramadol was associated with an increased risk of bleeding ulcer (adjusted odds ratio (aOR) 2.1, 95% confidence interval: (2.0–2.3). The association was stronger for newly initiated treatment with tramadol 2.8 (2.5–3.2) and weaker for ongoing treatment 1.7 (1.6–1.9). Codeine was also associated with an increased risk of bleeding ulcer 1.9 (1.7–2.1) and this association was also stronger for newly initiated treatment with codeine 2.3 (2.0–2.6) and weaker for ongoing treatment 1.7 (1.5–1.9). CONCLUSION: Treatment with tramadol was associated with an increased risk of bleeding peptic ulcer. Most of this association may be mediated by factors related to the pain condition rather than the pharmacologic effect per se.